PEMANFATAAN MEDIA SOSIAL PT. RIAU ANDALAN PULP AND PAPER DALAM MENINGKATKAN CITRA MELALUI PRINSIP 5 C - Bertina P. Batuara; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Technology of communication which has been progressed very rapidly is used by PT  Riau Andalan Pulp and Paper, an international companies. This company is prone to bad issues related to policies and environmental conditions, whereas in fact PT RAPP is based on the 5C principle that pioneered by Mr. Sukanto Tanoto as the company founder. The task of PT RAPP’s Digital Media Team is to present the company's operational activities through social media platforms, which are Twitter, Instagram and Facebook. The purpose of this study is to find out the systematic planning of Digital Media team and Social Media Managers, the potential of social media to improve the company’s image through the usage of social media and the impact of the 5C principles of PT.RAPP.               This study uses qualitative research method with an exploratory approach. The data which used on this study was ontained by  observation, interviews, and documentation. There are six informants in this study that chosen based on purposive technique. To check the validity, the  writer used a triangulation technique.               The results of this study are that PT RAPP's social media is useful in improving the image of company that has planning system which arranged by Digital Media Team and Social Media Manager. It's role are preparing contents for every week and month (content plan), monitoring and improving content performance (schedule monitoring), reading trends and predicting (benchmarking) and in practice there are other role as Anlyst Data. There are 3 potential things provided by PT RAPP's social media, which are: fast, near and real time. The impact of the 5C principle has been felt by the surrounding community (Good for community), the company tries to protect the environment in a sustainable manner (Good for Climate), Paper one is a product that has received certificates of national and international standards (Good for Customer) and the company is following the  regulations as a Responsible and Sustainable company (Good for Country), and all these impact at least give benefit for company (Good for Company). Keyword : Social Media, Image, Princip 5C